Novel micro-flat springs using the superior elastic properties of metallic glass foils - Yousfi, M. A.; Panagiotopoulos, Nikolaos T.; Jorge Junior, A. M.; Georgarakis, Konstantinos; Yavari, A. R. (Elsevier, 2017)
A thin metallic glass foil of 100 mg mass forming a sinusoidal arc behaves as non-conventional flat micro-spring withstanding loads 105 times higher than its load. Upon a normal load applied on the top of the arc, the foil deforms elastically leading to sinusoidal wavy patterns of higher order. The lifespan of the novel spring is higher than conventional low cycle springs and can potentially be further improved by eliminating surface and edge preparation induced defects. This unique behavior of metallic glass foils has the potential to revolutionize the field of springs and can be exploited for numerous applications.
Keywords: Metallic glasses; Wavy elastic response; Buckling; Flat micro springs; Fatigue resistance